1983
DOI: 10.1080/01652176.1983.9693891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection site on the bioavailability of an oxytetracycline formulation in ruminant calves

Abstract: SUMMARY The oxytetracycline (OTC) disposition was studied in a group of six calvesfollowing the administration of an oxytetracycline-10 per cent formulation (i) intravenously (i.v.), (ii) subcutaneously (s.c.) in the lateral neck, and intramuscularly (i.m.) in (iii) the lateral neck, (iv) the shoulder (M. triceps brachii), and (v) the buttock (M. semitendineus). The dose levels used for the intravenous route and other routes were respectively 17.0 ± 2.3 and 18.3 ± 1.25 mg OTC/ kg. The peak OTC concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 8 publications
(3 reference statements)
2
22
1
Order By: Relevance
“…The serum concentration–time profile of oxytetracycline, using a high strength depot formulation, was similar to those reported in earlier studies with the same dosage of 20 mg/kg administered intramuscularly (Brentnall et al., ; Davey, Ferber, & Kaye, ; El Korchi, Prats, Arboix, & Perez, ; Mestorino, Marino Hernandez, Marchetti, & Errecalde, ; Nouws & Vree, ; Toutain & Raynaud, ). Toutain and Raynaud () reported that oxytetracycline absorption occurred in two phases: the first was rapid and the second slower phase led to a flip‐flop PK profile.…”
Section: Discussionsupporting
confidence: 85%
“…The serum concentration–time profile of oxytetracycline, using a high strength depot formulation, was similar to those reported in earlier studies with the same dosage of 20 mg/kg administered intramuscularly (Brentnall et al., ; Davey, Ferber, & Kaye, ; El Korchi, Prats, Arboix, & Perez, ; Mestorino, Marino Hernandez, Marchetti, & Errecalde, ; Nouws & Vree, ; Toutain & Raynaud, ). Toutain and Raynaud () reported that oxytetracycline absorption occurred in two phases: the first was rapid and the second slower phase led to a flip‐flop PK profile.…”
Section: Discussionsupporting
confidence: 85%
“…In this trial, conducted on 30 calves, adverse reactions were limited to one case of anaphylaxis and two cases of injection site swellings. However, reduced bioavailability and prolonged plasma concentrations from tissue irritation can be seen in intramuscular injections in the hindquarters of calves (Nouws & Vree, 1983;Nouws et al, 1990). so increasing the dose may not be a viable option in fallow deer.…”
Section: *Harmonic Meanmentioning
confidence: 95%
“…and Gram-negative ( Escherichia coli ) infections in animals (13). OTC is a tetracycline derivative produced by Streptomyces rimosus (4, 5).…”
Section: Introductionmentioning
confidence: 99%